Agricultural by-product suitability for the production of chitinous composites and nanofibers utilising Trametes versicolor and Polyporus brumalis mycelial growth. (May 2019) - Jones, Mitchell P.; Lawrie, Ann C.; Huynh, Tien T.; Morrison, Paul D.; Mautner, Andreas; Bismarck, Alexander; John, Sabu
Graphical abstract: Highlights: Agricultural by-products upcycled into chitin using enzymatic fungal growth. Fungal macrofibers with chitin-glucan nanofibers produced under ambient conditions. Sugarcane by-product molasses more effective than laboratory nutrient malt extract. Cheap, renewable, easily-isolated, abundant alternative to crustacean chitin. Abstract: Agricultural by-products can be upcycled into environmentally-sustainable, inexpensive chitinous materials and nanofibers derived from fungal mycelium for composites, cosmetics, pharmaceuticals and water treatment applications. This study determined the suitability of common agricultural by-products as medium for fungal growth. Growth was measured by quantifying ergosterol, a unique fungal product, in solid and liquid media. The results reveal that fungi grew less on rice hull, sugarcane bagasse and wheat straw agricultural by-products than on commercial wheat grains. However, the liquid agricultural by-product blackstrap molasses facilitated very high biomass production, outperforming the commonly used laboratory nutrient malt extract. Hyphal fusion, sheet formation and hyphal diameter metrics of fungi growing on each substrate were evaluated by SEM to assess suitability for chitin nanofiber production. Utilising these materials offers a cheap, renewable, easily-isolated, and abundant alternative to problematic crustacean chitin that when implemented on a large scale could rapidly upcycle low-value agricultural by-products into high-value chitinous materials.